Pengaruh Akuntabilitas Publik, Kejelasan Sasaran Anggaran Dan Partisipasi Anggaran Terhadap Kinerja Manajerial - Putri Melia; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to see the effect of public accountability, the clarity of budget targets and budget participation on the performance of managerial unit of local Solok regency of the Southern Regency. The population in this study is the whole SKPD Southern Southern District of 28 SKPD with 82 respondents. The sample in this study uses total technique sampling. Methods of analysis used are multiple linear regression analysis. The results of this study indicate that public accountability and clarity of budget targets affect the performance of managerial unit of local Solok Regency of the Southern District. While the budget participation has no effect on the managerial performance of the Unit of Southern Southern District Unit.